2011
DOI: 10.1063/1.3602316
|View full text |Cite
|
Sign up to set email alerts
|

Structural origins of relaxor behavior in a 0.96(Bi1/2Na1/2)TiO3–0.04BaTiO3 single crystal under electric field

Abstract: Diffuse x-ray scattering intensities from a single crystal of 0.96(Bi1/2Na1/2TiO3)–0.04(BaTiO3) have been collected at room temperature with and without application of an electric field along the [100] direction. Distinct features in the diffuse scattering intensities indicate correlations on a nanometer length scale. It is shown that locally correlated planar-like structures and octahedral tilt-domains within the room temperature rhombohedral R3c phase are both electrically active and are irreversibly affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 20 publications
7
38
0
Order By: Relevance
“…Kreisel et al showed from in situ high-energy X-ray diffraction experiments that application of hydrostatic pressure up to 2.8 GPa first leads to decrease in the intensity of the asymmetric diffuse scattering peaks in Na 0.5 Bi 0.5 TiO 3 single crystals, and finally to their eventual disappearance (Figure 8a) under 3.7 GPa [45]. Similar decrease in intensities of L-shaped asymmetric diffuse scattering peaks could also be observed in Na 0.5 Bi 0.5 TiO 3 single crystals under applied electric fields (Figure 8b) [78,79]. Such observations indicated that the structural differences between the matrix and the nanoscales inclusions could be irreversibly overcome by application of mechanical pressure or electric fields, ultimately leading to a phase transition in the short-range order associated with nanoscale inclusions.…”
Section: Octahedral Tilt Disordersupporting
confidence: 67%
“…Kreisel et al showed from in situ high-energy X-ray diffraction experiments that application of hydrostatic pressure up to 2.8 GPa first leads to decrease in the intensity of the asymmetric diffuse scattering peaks in Na 0.5 Bi 0.5 TiO 3 single crystals, and finally to their eventual disappearance (Figure 8a) under 3.7 GPa [45]. Similar decrease in intensities of L-shaped asymmetric diffuse scattering peaks could also be observed in Na 0.5 Bi 0.5 TiO 3 single crystals under applied electric fields (Figure 8b) [78,79]. Such observations indicated that the structural differences between the matrix and the nanoscales inclusions could be irreversibly overcome by application of mechanical pressure or electric fields, ultimately leading to a phase transition in the short-range order associated with nanoscale inclusions.…”
Section: Octahedral Tilt Disordersupporting
confidence: 67%
“…A large increase in apparent permittivity and loss with temperature is observed in the 0.5 at% Fe sample for low frequencies ( states, consistent with relaxor-type behavior. 33,34 The peak in the loss tangent vs. temperature plot is at 176 ºC for unmodified NBT and at 202 ºC for 0.5 at% Fe modified NBT (Table I).…”
Section: A Temperature Dependence Of Propertiesmentioning
confidence: 99%
“…Single crystals of BNT-BT have been grown and the influence on dc-bias E on the phase stability [36] and the diffuse X-ray scattering [37] have been investigated. Recently, a bifurcated polarization rotation model in BNT has been postulated by a neutron pair distribution analysis [38] and the piezoelectric response is suggested to originate from a polarization rotation.…”
Section: Open Accessmentioning
confidence: 99%